A-173 Grey Matter Volume, Psychotic Disorders, And Heredity of Alcohol Use Disorder: Reconceptualization by B-SNIP Biotypes. (17th August 2022) - Pietrzykowski, Malvina O; Waters, Abigail B; Gansler, David A; Jerram, Matthew; Pearlson, Godfrey D; Tamminga, Carol A; Clementz, Brett A; Keshavan, Matcheri S; Gershon, Elliot S
Abstract: Objective: Bipolar and Schizophrenia Network for Intermediate Phenotypes (B-SNIP) researchers have proposed three Biotypes that show advantages of a dimensional approach to classification, revealing different levels of dysfunction severity through EEG and various forms of cognitive testing. Although preliminary work has been done showing neuroanatomical differences among the biotypes and patterns of heredity, more research is required to investigate the contribution of significant co-morbid factors such as alcohol misuse. Objective. Neuroanatomical data were used to further understand the biomarker of grey matter volume (GMV) in relation to the B-SNIP Biotypes and the interacting influence of family history of alcohol use disorder (FH-AUD). Method. Biotype, FH-AUD, and demographic variables (age, sex, education, and ethnicity) were used in hierarchical regression analyses for prediction of total volume and two key regions (superior parietal cortex and posterior cingulate cortex) in stable probands (n = 347) and their healthy first-degree relatives (n = 346) separately. Prediction was also analyzed in the context of conventional diagnosis of psychotic disorders (schizophrenia, schizoaffective disorder, and bipolar disorder with psychotic features). Structural data were analyzed using FreeSurfer. Results. Biotype was shown to be a more robust predictor of GMV than diagnosis both generally and specifically in relevant regions (p < .05). A pattern of GMV reduction based on severity was observed both in probands and relatives. Effects of FH-AUD and its interaction with Biotype were occasionally observed. Conclusions. This study contributes to the efforts of psychobiological research to establish a more valid conceptualization of psychological disorders through biological mechanisms.